2023
DOI: 10.3389/fcell.2023.1196684
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and transcriptomic alterations in the ClC-3-deficient mice consuming a normal diet

Abstract: Introduction: Metabolic disorders are an important health concern that threatens life and burdens society severely. ClC-3 is a member of the chloride voltage-gated channel family, and ClC-3 deletion improved the phenotypes of dysglycemic metabolism and the impairment of insulin sensitivity. However, the effects of a healthy diet on transcriptome and epigenetics in ClC-3−/− mice were not explained in detail.Methods: Here, we performed transcriptome sequencing and Reduced Representation Bisulfite Sequencing for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(60 reference statements)
1
0
0
Order By: Relevance
“…In our study, the body weight of Clcn3 −/− mice was also significantly lower than that of Clcn3 +/+ mice at the age of 4 weeks, but a lack of significant differences between the two groups at 8, 12, 16, and 20 weeks old when fed a normal diet. This result ( Figure 1 ) indicated that the effect of Clcn3 on the body weight of mice with a normal diet was mainly at a young age, our previous article also showed a similar result ( 16 ). Clcn3 knockout delays the growth and development of mice.…”
Section: Discussionsupporting
confidence: 68%
“…In our study, the body weight of Clcn3 −/− mice was also significantly lower than that of Clcn3 +/+ mice at the age of 4 weeks, but a lack of significant differences between the two groups at 8, 12, 16, and 20 weeks old when fed a normal diet. This result ( Figure 1 ) indicated that the effect of Clcn3 on the body weight of mice with a normal diet was mainly at a young age, our previous article also showed a similar result ( 16 ). Clcn3 knockout delays the growth and development of mice.…”
Section: Discussionsupporting
confidence: 68%